Are men who have sex with men at higher risk for HIV in Latin America more aware of PrEP? - Ryan D Assaf (Public Library of Science (PLoS), 2021)
Introduction PrEP awareness in Latin America has been poorly characterized, with studies in Brazil, Mexico, and Peru highlighting awareness of 65% among gay, bisexual and other men who have sex with men (MSM). We assessed the association between higher risk of HIV infection, indicative of PrEP eligibility, and PrEP awareness among MSM from these countries. Methods This was a secondary analysis of a web-based survey advertised on social media platforms from March-June 2018 in Brazil, Mexico and Peru. Eligible individuals were cisgender MSM, ≥18 years old, HIV negative or of unknown status, who lived in these countries, and provided informed consent. Higher risk of HIV infection was defined as having 10 or more points in the HIV Risk Index for MSM (HIRI-MSM). We used multivariable Poisson regression models to calculate adjusted prevalence ratios (aPR) testing the association between higher risk for HIV and PrEP awareness. Results After exclusions, 19,457 MSM were included in this analysis. In Brazil, 53.8% were classified as higher risk for HIV, 51.9% in Mexico, and 54.2% in Peru. Higher risk for HIV was minimally associated with PrEP awareness among those in Brazil (aPR 1.04, 95% CI 1.01, 1.06), but no such association was observed in Mexico or Peru. Having more than a high school education, high income, daily use of geosocial networking (GSN) applications, and substance use were associated with PrEP awareness. Conclusion Higher risk of HIV infection was associated with increased PrEP awareness in Brazil. However, this association was weak indicating that PrEP awareness could be strengthened with further prevention efforts. In the remaining countries, results were non-conclusive between risk and awareness. Interventions to increase PrEP awareness are paramount to increase PrEP willingness and uptake and in turn prevent new HIV infections. Social media platforms could play an important role to achieve this goal.